Fundamentální analýza akciové společnosti PHILIP MORRIS ČR a.s. - Kubínová, Martina (Univerzita Pardubice, 2006)
Předmětem diplomové práce je fundamentální analýza akcie Philip Morris ČR a.s. V první části byly vymezeny základní přístupy akciových analýz s důrazem na fundamentální analýzu. Druhá část byla věnována praktickému provedení fundamentální analýzy pro akcii Philip Morris ČR a.s. K jejímu zpracování byl zvolen postup down to top. Nejprve byla provedena finanční analýza a výpočet vnitřní hodnoty akcie. Pokračovalo se odvětvovou a globální analýzou. Výsledek celé analýzy byl shrnut do investičního doporučení, které bylo zkonstruováno tak, aby se investor mohl na základě nejdůležitějších informací rychle rozhodnout o své investiční strategii.

The subject of the thesis is the fundamental analysis of the share of the company Philip Morris ČR a.s. At first, the basic types of share analyses are explained. The special stress is put on fundamental analysis. The second part is dedicated to the fundamental analysis of the share of the company Philip Morris ČR a. s. To describe this part, the method "down to top" was chosen. First of all, the financial analysis was compiled, and then the fair value of the share was stated, followed by the segment and global analysis at the end. The results of the thesis are summarized into investment recommendation. This is presented with the intention to help the investor to decide more efficiently, based on the most important market information, about his investment strategy.
The fundamental analysis of the share of the company PHILIP MORRIS ČR a.s.
Keywords: fundamental analysis; technical analysis; psychological analysis; theory of market efficiency; Financial analysis; fundamentální analýza; technická analýza; psychologická analýza; efektivní trhy; Finanční analýza; Philip Morris ČR a.s